A Study on Emotional Maturity of Xi-Standard Students - J. , Vigneshwari; P., Senthamizh Pavai (International Journal of Psychosocial Rehabilitation, 2020)
A life filled with maturity, self-confidence, and fulfillment leads to success. Maturity refers to a significant phase in the growth of a living organism, especially when there is a striking difference of forces between adolescent and mature emotional attitudes like insecurity, awkwardness, instability, etc., and Emotions are great motivating forces throughout the span of human life, which affects the aspirations, actions, and thoughts of the individual. It is observed through thoughts and behaviors, which means almost all kinds of emotions (positive as well as negative), and is able to express them skillfully, timely, and in different situations of life. Emotions are important in every stage of life, which plays the maximum role during the adolescence period. It gives the clue to the essence of the mature state of mind by understanding them. In school education, particularly high school education, plays an important role in personal and professional success. Hence, one needs to adjust to the existing and continuously changing environments. The present study consisted of 200 students drawn randomly from different schools in Chennai and Thiruvallur districts. The tool used to collect data for the study was the Emotional Maturity Scale and a personal data sheet. t-tests, ANOVA, and chi-square tests showed that there exists a difference and association with emotional maturity and gender.